Creative Industry Competitiveness in Indonesia (Study on Creative Industry Map) - Subagja, Iwan Kurniawan (International Conferences SDGs 2030 Challenges and Solutions, 2030)
The Department of Commerce has determined the economy in the creative industry into 14 (fourteen) sectors: (1) advertising services, (2) architecture, (3) art and antiques market, (4) craft, (5) design, (6) fashion, (7) video, film and photography, (8) interactive games (9) music, (10) performing arts, (11) publishing and printing, (12) computer and software services, (13) television and radio, (14) research and development. Mapping of creative industrial areas is done so that the process of guidance and distribution of assistance from local and central government and the management of the creative industries from each region focused so that the regions have characteristics in producing the creative industry and can compete in the current era of globalization. Creative industry in Indonesia began to mushroom in 2007, but many people still do not understand what sectors are included into the creative industry and its development. With so many people's lack of understanding of the creative industry, it makes its own homework for the government to socialize the creative industries so that the government seeks to map the creative industries in Indonesia. Though the creative industry is able to contribute greatly to the Gross Domestic Product (GDP) of an area and create jobs. This study aims to further understand the characteristics of creative industries, as well as to identify the constraints and opportunities faced by creative industry players in Indonesia. To identify and analyze the creative industries used 4 quadrant statistical methods Location Quadrant (LQ) and Dynamic Location Quotient (DLQ). This study uses secondary data of large and medium industry statistics as well as small and micro industries in 2010-2013 at Provincial level obtained from the Central Bureau of Statistics (BPS). The results of this mapping study will provide a general overview of the creative industries sector that has competitiveness in every region or province in Indonesia.